Lightweight high-toughness SiO2 aerogel heat-insulation composite material and preparation method thereof
By using components such as carbon fiber and tetraethyl silicate in SiO2 aerogel, combined with specific preparation methods, the problems of fragility and low strength of SiO2 aerogel are solved, and lightweight, high-strength thermal insulation composite materials are realized , has good thermal insulation performance and temperature resistance, and is suitable for a variety of environments.
Patent Information
- Application Number
- CN202411560720.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-03
AI Technical Summary
The fragility and low strength of SiO2 aerogel lead to poor mechanical properties in practical applications, and the existing fiber reinforced composite materials are dense, which cannot effectively solve the problems of lightweight flexibility and high temperature resistance.
Using carbon fiber as the framework, using tetraethyl silicate containing ester groups as the silicon source, combined with anhydrous ethanol, hydrochloric acid, deionized water, dilute ammonia water and carbon fiber felt, lightweight and high tough SiO2 is prepared through a specific mixing and impregnation process. Aerogel thermally insulated composite materials, including immersion aging and drying steps to improve the mechanical properties of the material.
It achieves good thermal insulation performance and temperature resistance, reduces the cost of use of aerogels, solves the problems of low strength and brittleness of traditional SiO2 aerogels, and provides high flexibility and low density composite materials suitable for Low and high temperature environment.
Smart Images

Figure CN119241205A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aerogels, and in particular to a lightweight and high-toughness SiO2 aerogel thermal insulation composite material and a preparation method thereof. Background Art
[0002] Aerogel is a low-density, nanoporous, amorphous material with a continuous three-dimensional network structure that provides efficient thermal insulation. SiO2 aerogel is composed of interconnected nanoscale SiO2 particles, forming a nanoscale skeleton and pores. The nanoscale pores within the aerogel are smaller than the average self-path of air molecules, effectively preventing convection. The abundant pore walls effectively reduce radiative heat transfer, while the pearl-chain-like structure reduces heat conduction. SiO2 aerogel has an ultra-low density and extremely low thermal conductivity, making it widely used in construction, aerospace, weaponry, and other fields.
[0003] SiO2 aerogels have a pearl-necklace-like, three-dimensional network structure. Their secondary particles are connected by point contacts, resulting in small contact areas and weak bonds, leading to poor mechanical properties. When the aerogel is subjected to external stress, the contact points between the secondary particles break, causing the connections between the particles to become disconnected and the gel skeleton to collapse. Therefore, the inherent fragility and low strength of SiO2 aerogels have severely hampered their practical applications.
[0004] The mechanical properties of fiber-reinforced SiO2 aerogel composite materials are commonly used. For example, Patent No. CN116813304A discloses a basalt fiber-reinforced aerogel composite material atmospheric pressure drying process, which uses methyl orthosilicate as the silicon source and basalt fiber as the reinforcing fiber to obtain a composite aerogel composite material. However, the inorganic fiber is brittle and has a high density, resulting in poor mechanical properties of the composite material and the loss of advantages such as low density of the material.
[0005] Therefore, there is an urgent need to design a SiO2 aerogel composite material that is lightweight, flexible, and resistant to high temperatures. Summary of the Invention
[0006] The purpose of the present invention is to solve at least one of the technical problems existing in the prior art and to provide a lightweight and high-toughness SiO2 aerogel thermal insulation composite material and a preparation method thereof.
[0007] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is as follows: a lightweight and high-toughness SiO2 aerogel thermal insulation composite material, made of the following components in parts by weight, including 1 to 2 parts of carbon fiber, 11 to 20 parts of ester-containing silicon source, 13 to 25 parts of solvent, 3 to 7 parts of hydrolyzing agent, 0.1 to 0.3 parts of acidic catalyst, and 3 to 9 parts of alkaline catalyst; wherein the carbon fiber is a polyacrylonitrile-based (PAN) carbon fiber felt, asphalt-based carbon fiber felt, or viscose-based carbon fiber felt that has not been sizing and surface treated.
[0008] Furthermore, the ester-containing silicon source is tetraethyl silicate.
[0009] Furthermore, the solvent is anhydrous ethanol.
[0010] Furthermore, the hydrolyzing agent is deionized water.
[0011] Furthermore, the acidic catalyst is hydrochloric acid; and the alkaline catalyst is aqueous ammonia.
[0012] A method for preparing a lightweight and high-tough SiO2 aerogel thermal insulation composite material. The method for preparing the lightweight and high-tough SiO2 aerogel thermal insulation composite material is as follows:
[0013] S1. Mix the raw materials according to the above parts by weight, heat, and stir to form a mixed solution;
[0014] S2. Pour the mixed solution obtained in step S1 into a mold containing carbon fiber felt, and fully fill the carbon fiber felt with the mixed solution by manual impregnation to perform gel treatment, thereby obtaining a composite material;
[0015] S3. After the composite material is gelled, it is demoulded and placed in an organic solvent for immersion aging;
[0016] S4. After the soaking is completed, the mixture is dried to obtain a lightweight and high-toughness SiO2 aerogel thermal insulation composite material.
[0017] Furthermore, step S3 of placing in an organic solvent for soaking and aging includes placing in anhydrous ethanol for soaking and aging for 24 hours.
[0018] Furthermore, step S3 of immersing in an organic solvent for aging further includes immersing in n-hexane for 24 hours, where the volume of n-hexane is 4 to 5 times the volume of the composite material.
[0019] Furthermore, step S3 of immersing in an organic solvent for aging further includes immersing in a mixed solution of n-hexane and trimethylchlorosilane for 24 hours, wherein the volume of n-hexane is 4 to 5 times the volume of the composite material, and the volume of trimethylchlorosilane is 0.2 times the volume of the composite material.
[0020] Furthermore, in step S4, drying includes drying the soaked composite material at 80° C. for 4 hours and 120° C. for 4 hours until constant weight is reached.
[0021] Compared with the existing technology, the technical solution of this application has the following beneficial effects:
[0022] 1. The lightweight and high-toughness SiO2 aerogel thermal insulation composite material of the present invention has good thermal insulation performance and temperature resistance. It uses carbon fiber as the skeleton to solve the poor mechanical properties of traditional silica aerogel (low strength, high brittleness, and product powdering and slag falling), reducing the use of aerogel and lowering costs.
[0023] 2. The lightweight and high-toughness SiO2 aerogel thermal insulation composite material of the present invention can be used for thermal insulation in low-temperature materials and thermal insulation in high-temperature environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a schematic diagram of the structure of the composite material attached to the side of the cylinder in the preferred embodiment 1 of the present invention;
[0025] Figure 2 This is a schematic diagram of the structure of the composite material attached to the side of the cylinder in the preferred embodiment 2 of the present invention;
[0026] Figure 3 This is a schematic structural diagram of the composite material adhered to the side of a cylinder in preferred embodiment 3 of the present invention. DETAILED DESCRIPTION
[0027] The technical solutions of the present invention will be described clearly and completely below with reference to the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0028] Example 1
[0029] A lightweight and high-toughness SiO2 aerogel thermal insulation composite material is made from the following raw materials in parts by weight: 15.0 parts of tetraethyl silicate, 20.0 parts of anhydrous ethanol, 0.2 parts of 1 mol / L hydrochloric acid, 5.0 parts of deionized water, 1 part of carbon fiber felt, and 6.0 parts of 0.25 mol / L dilute ammonia water.
[0030] The preparation method of the lightweight and high-toughness SiO2 aerogel thermal insulation composite material comprises the following steps:
[0031] Step 1: Weigh 15.0 parts of tetraethyl silicate with a purity of more than 99%, 20.0 parts of analytical grade anhydrous ethanol, and 5.0 parts of deionized water into a three-necked flask;
[0032] Step 2: Weigh 0.2 parts of 1 mol / L hydrochloric acid solution and add it to the three-necked flask in step 1. Stir the mixture evenly and adjust the pH of the mixture to about 2.
[0033] Step 3: Heat the three-necked flask containing the mixed solution in step 2 to 80° C. in a water bath or oil bath, adjust the stirring speed to 250 r / min, and stir for 2 h to fully hydrolyze;
[0034] Step 4: After the hydrolysis reaction is completed, heating is stopped and the reaction system is cooled to room temperature;
[0035] Step 5: Place the cut carbon fiber felt in a 60mm*60mm*10mm rectangular parallelepiped mold;
[0036] Step 6: Pour the cooled hydrolyzate into a beaker, add a magnet, place it on a magnetic stirrer and start stirring;
[0037] Step 7: Add 6.0 parts of 0.25 mol / L dilute ammonia water to the hydrolyzed solution being stirred in step 6 to adjust the pH of the mixture to 7, and continue to stir thoroughly for 1 minute;
[0038] Step 8: Pour the mixture stirred in step 7 into the mold to which the carbon fiber felt has been added in advance in step 5;
[0039] Step 9: The sol is fully filled into the carbon fiber felt by manual impregnation. After 1-2 minutes, the sol turns into gel, and the gelation is completed;
[0040] Step 10: The gel obtained in step 9 and the carbon fiber composite material are sealed in a mold and placed at 25° C. for about 10 minutes to further harden the gel;
[0041] Step 11: After the gel is hardened, it is demoulded and placed in anhydrous ethanol that can completely immerse the composite material for immersion aging at 25° C. for 24 hours;
[0042] Step 12: Place the silicone gel composite material aged in step 11 into n-hexane and soak it in a 25° C. environment for 24 hours to perform solvent replacement. The volume of n-hexane is 4 to 5 times the volume of the composite material.
[0043] Step 13: soak the composite material after solvent replacement in step 12 in a mixed solution of n-hexane and trimethylchlorosilane for 24 hours for hydrophobic modification, wherein the volume of n-hexane is 4 to 5 times the volume of the composite material, and the volume of trimethylchlorosilane is 0.2 times the volume of the composite material.
[0044] Step 14: bake the composite material subjected to hydrophobic modification in step 13 at 80° C. for 4 h and 120° C. for 4 h to constant weight, respectively, to obtain a carbon fiber / SiO 2 aerogel composite material.
[0045] The thermal conductivity of the carbon fiber / SiO2 aerogel composite material obtained above was measured to be 0.015W / (m·K) at 25°C and the density was 0.16g / cm 3 , Figure 1 The medium material can be completely attached to the side of a cylinder with a diameter of 2.5 cm without cracks or falling off, and has high flexibility.
[0046] Example 2
[0047] A lightweight and high-toughness SiO2 aerogel thermal insulation composite material is prepared from the following raw materials in parts by weight: 13.7 parts of tetraethyl silicate, 21.6 parts of anhydrous ethanol, 0.2 parts of 1 mol / L hydrochloric acid, 4.6 parts of deionized water, 1 part of carbon fiber felt, and 6.4 parts of 0.25 mol / L dilute ammonia water.
[0048] The preparation method of the lightweight and high-toughness SiO2 aerogel thermal insulation composite material comprises the following steps:
[0049] Step 1: Weigh 13.7 parts of tetraethyl silicate with a purity of more than 99%, 21.6 parts of analytical grade anhydrous ethanol, and 4.6 parts of deionized water into a three-necked flask;
[0050] Step 2: Weigh 0.2 parts of 1 mol / L hydrochloric acid solution and add it to the three-necked flask in step 1. Stir the mixture evenly and adjust the pH of the mixture to about 2.
[0051] Step 3: Heat the three-necked flask containing the mixed solution in step 2 to 80° C. in a water bath or oil bath, adjust the stirring speed to 250 r / min, and stir for 2 h to fully hydrolyze;
[0052] Step 4: After the hydrolysis reaction is completed, heating is stopped and the reaction system is cooled to room temperature;
[0053] Step 5: Place the cut carbon fiber felt in a 60mm*60mm*10mm rectangular parallelepiped mold;
[0054] Step 6: Pour the cooled hydrolyzate into a beaker, add a magnet, place it on a magnetic stirrer and start stirring;
[0055] Step 7: Add 6.4 parts of 0.25 mol / L dilute ammonia water to the hydrolyzed solution being stirred in step 6 to adjust the pH of the mixture to 7, and continue to stir thoroughly for 1 minute;
[0056] Step 8: Pour the mixture stirred in step 7 into the mold to which the carbon fiber felt has been added in advance in step 5;
[0057] Step 9: Manually impregnate the sol into the carbon fiber felt. After 1-2 minutes, the sol turns into gel, and the gelation is completed.
[0058] Step 10: The gel obtained in step 9 and the carbon fiber composite material are sealed in a mold and placed at 25° C. for about 10 minutes to further harden the gel;
[0059] Step 11: After the gel is hardened, it is demoulded and placed in anhydrous ethanol that can completely immerse the composite material for immersion aging at 25° C. for 24 hours;
[0060] Step 12: Place the silicone gel composite material aged in step 11 into n-hexane and soak it in a 25° C. environment for 24 hours to perform solvent replacement. The volume of n-hexane is 4 to 5 times the volume of the composite material.
[0061] Step 13: soak the composite material after solvent replacement in step 12 in a mixed solution of n-hexane and trimethylchlorosilane for 24 hours for hydrophobic modification, wherein the volume of n-hexane is 4 to 5 times the volume of the composite material, and the volume of trimethylchlorosilane is 0.2 times the volume of the composite material.
[0062] Step 14: bake the composite material subjected to hydrophobic modification in step 13 at 80° C. for 4 h and 120° C. for 4 h to constant weight, respectively, to obtain a carbon fiber / SiO 2 aerogel composite material.
[0063] The thermal conductivity of the carbon fiber / SiO2 aerogel composite material obtained above was measured to be 0.014 W / (m·K) at 25°C and the density was 0.15 g / cm 3 , Figure 2 The medium material can be completely attached to the side of a cylinder with a diameter of 2.5 cm without cracks or falling off, and has high flexibility.
[0064] Example 3
[0065] A lightweight and high-toughness SiO2 aerogel thermal insulation composite material is prepared from the following raw materials in parts by weight: 12.9 parts of tetraethyl silicate, 22.7 parts of anhydrous ethanol, 0.2 parts of 1 mol / L hydrochloric acid, 4.3 parts of deionized water, 1 part of carbon fiber felt, and 6.6 parts of 0.25 mol / L dilute ammonia water.
[0066] The preparation method of the lightweight and high-toughness SiO2 aerogel thermal insulation composite material comprises the following steps:
[0067] Step 1: Weigh 12.9 parts of tetraethyl silicate with a purity of more than 99%, 22.7 parts of analytical grade anhydrous ethanol, and 4.3 parts of deionized water into a three-necked flask;
[0068] Step 2: Weigh 0.2 parts of 1 mol / L hydrochloric acid solution and add it to the three-necked flask in step 1. Stir the mixture evenly and adjust the pH of the mixture to about 2.
[0069] Step 3: Heat the three-necked flask containing the mixed solution in step 2 to 80° C. in a water bath or oil bath, adjust the stirring speed to 250 r / min, and stir for 2 h to fully hydrolyze;
[0070] Step 4: After the hydrolysis reaction is completed, heating is stopped and the reaction system is cooled to room temperature;
[0071] Step 5: Place the cut carbon fiber felt in a 60mm*60mm*10mm rectangular parallelepiped mold;
[0072] Step 6: Pour the cooled hydrolyzate into a beaker, add a magnet, place it on a magnetic stirrer and start stirring;
[0073] Step 7: Add 6.6 parts of 0.25 mol / L dilute ammonia water to the hydrolyzed solution being stirred in step 6 to adjust the pH of the mixture to 7, and continue to stir thoroughly for 1 minute;
[0074] Step 8: Pour the mixture stirred in step 7 into the mold to which the carbon fiber felt has been added in advance in step 5;
[0075] Step 9: The sol is fully filled into the carbon fiber felt by manual impregnation. After 1-2 minutes, the sol turns into gel, and the gelation is completed;
[0076] Step 10: The gel obtained in step 9 and the carbon fiber composite material are sealed in a mold and placed at 25° C. for about 10 minutes to further harden the gel;
[0077] Step 11: After the gel is hardened, it is demoulded and placed in anhydrous ethanol that can completely immerse the composite material for immersion aging at 25° C. for 24 hours;
[0078] Step 12: Place the silicone gel composite material aged in step 11 into n-hexane and soak it in a 25° C. environment for 24 hours to perform solvent replacement. The volume of n-hexane is 4 to 5 times the volume of the composite material.
[0079] Step 13: soak the composite material after solvent replacement in step 12 in a mixed solution of n-hexane and trimethylchlorosilane for 24 hours for hydrophobic modification, wherein the volume of n-hexane is 4 to 5 times the volume of the composite material, and the volume of trimethylchlorosilane is 0.2 times the volume of the composite material.
[0080] Step 14: bake the composite material subjected to hydrophobic modification in step 13 at 80° C. for 4 h and 120° C. for 4 h to constant weight, respectively, to obtain a carbon fiber / SiO 2 aerogel composite material.
[0081] The thermal conductivity of the carbon fiber / SiO2 aerogel composite material obtained above was measured to be 0.015W / (m·K) at 25°C and the density was 0.15g / cm 3 , Figure 3 The medium material can be completely attached to the side of a cylinder with a diameter of 2.5 cm without cracks or falling off, and has high flexibility.
[0082] Other embodiments:
[0083] The invention is prepared from the following raw materials in parts by weight: 19.9 parts of tetraethyl silicate, 13.2 parts of anhydrous ethanol, 0.3 parts of 1 mol / L hydrochloric acid, 6.6 parts of deionized water, 1 part of carbon fiber felt, and 3.6 parts of 0.25 mol / L dilute ammonia water.
[0084] 17.9 parts of tetraethyl silicate, 15.9 parts of anhydrous ethanol, 0.3 parts of 1 mol / L hydrochloric acid, 6.0 parts of deionized water, 1 part of carbon fiber felt, and 4.4 parts of 0.25 mol / L dilute ammonia water.
[0085] 16.3 parts of tetraethyl silicate, 18.0 parts of anhydrous ethanol, 0.2 parts of 1 mol / L hydrochloric acid, 5.4 parts of deionized water, 1 part of carbon fiber felt, and 5.2 parts of 0.25 mol / L dilute ammonia water.
[0086] 12 parts of tetraethyl silicate, 23.9 parts of anhydrous ethanol, 0.2 parts of 1 mol / L hydrochloric acid, 4.0 parts of deionized water, 1 part of carbon fiber felt, and 7.4 parts of 0.25 mol / L dilute ammonia water.
[0087] 11.25 parts of tetraethyl silicate, 24.9 parts of anhydrous ethanol, 0.2 parts of 1 mol / L hydrochloric acid, 3.7 parts of deionized water, 1 part of carbon fiber felt, and 8.2 parts of 0.25 mol / L dilute ammonia water.
[0088] Under the premise that no conflict occurs, those skilled in the art may freely combine and superimpose the above-mentioned additional technical features.
[0089] It will be understood that the present invention is described by way of some embodiments, and it will be appreciated by those skilled in the art that various changes or equivalent substitutions may be made to these features and embodiments without departing from the spirit and scope of the present invention. In addition, under the teachings of the present invention, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the spirit and scope of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of this application are intended to be protected by the present invention.
Claims
1. A lightweight and high-toughness SiO2 aerogel thermal insulation composite material, characterized in that: The invention is made of the following components in parts by weight, including 1 to 2 parts of carbon fiber, 11 to 20 parts of ester-containing silicon source, 13 to 25 parts of solvent, 3 to 7 parts of hydrolyzing agent, 0.1 to 0.3 parts of acidic catalyst and 3 to 9 parts of alkaline catalyst; wherein the carbon fiber is one of polyacrylonitrile-based (PAN) carbon fiber felt, asphalt-based carbon fiber felt and viscose-based carbon fiber felt which have not been sized and surface treated.
2. The lightweight and high-toughness SiO2 aerogel thermal insulation composite material according to claim 1, characterized in that: The ester-containing silicon source is tetraethyl silicate.
3. The lightweight and high-toughness SiO2 aerogel thermal insulation composite material according to claim 1, characterized in that: The solvent is anhydrous ethanol.
4. The lightweight and high-toughness SiO2 aerogel thermal insulation composite material according to claim 1, characterized in that: The hydrolyzing agent is deionized water.
5. The lightweight and high-toughness SiO2 aerogel thermal insulation composite material according to claim 1, characterized in that: The acidic catalyst is hydrochloric acid; the alkaline catalyst is ammonia water.
6. A method for preparing a lightweight and high-toughness SiO2 aerogel thermal insulation composite material, characterized in that: The method for preparing the lightweight and high-toughness SiO2 aerogel thermal insulation composite material according to any one of claims 1 to 5 is as follows: S1. Mix the raw materials according to the weight parts of claim 1, heat them, and stir them to form a mixed solution; S2, pouring the mixed solution obtained in step S1 into a mold with carbon fiber felt placed thereon, and fully filling the mixed solution into the carbon fiber felt by manual impregnation to perform gel treatment, thereby obtaining a composite material; S3, after the composite material is gelled, demoulding and placing it in an organic solvent for immersion aging; S4. After soaking, the mixture is dried to obtain a lightweight and high-toughness SiO2 aerogel thermal insulation composite material.
7. The method for preparing the lightweight and high-toughness SiO2 aerogel thermal insulation composite material according to claim 6, characterized in that: The step S3 of placing in an organic solvent for immersion aging includes placing in anhydrous ethanol for immersion aging for 24 hours.
8. The method for preparing the lightweight and high-toughness SiO2 aerogel thermal insulation composite material according to claim 6, characterized in that: The step S3 of placing in an organic solvent for immersion aging also includes placing in n-hexane for immersion for 24 hours, and the volume of n-hexane is 4 to 5 times the volume of the composite material.
9. The method for preparing the lightweight and high-toughness SiO2 aerogel thermal insulation composite material according to claim 6, characterized in that: The step S3 of placing in an organic solvent for immersion aging also includes placing in a mixed solution of n-hexane and trimethylchlorosilane for immersion for 24 hours, the volume of n-hexane is 4 to 5 times the volume of the composite material, and the volume of trimethylchlorosilane is 0.2 times the volume of the composite material.
10. The method for preparing the lightweight and high-toughness SiO2 aerogel thermal insulation composite material according to claim 6, characterized in that: The drying in step S4 includes drying the soaked composite material at 80° C. for 4 hours and 120° C. for 4 hours respectively until constant weight.
Citation Information
Cited By
Biomass-based carbon aerogel-polyacrylonitrile fiber composite thermal insulation material and preparation method thereof
CN121895060A
